PENGARUH MODELPEMBELAJARAN PICTURE AND PICTURE DAN MOTIVASI TERHADAP HASIL BELAJAR SENI RUPA SISWA KELAS VII SMP NEGERI 34 PADANG - OKTARIANI, Dr. Ramalis Hakim, M.Pd., Drs. Wisdiarman, M.Pd. (Universitas Negeri Padang, 2018)
The purpose of this research is to know the influence of learning model picture and picture and motivation toward student learning result in art class VII learning at SMPN 34 Padang. Quasi experimental method with 2x2 factorial research design become method in this research. Data collection was done through questionnaire instrument of learning motivation and learning result test. The population in this study is all students of class VII SMPN 34 Padang while the sample in this study is class VII3 and class VII4.Teknalalisi data in this study with t-test. Research findings show (1) Students learning outcomes are taught using Picture and Picture models differ significantly compared to those taught using conventional models, (2) Students' learning outcomes with high motivation are taught using the Picture and Picture model significantly different than using conventional models. (3) Students' learning outcomes with low motivation are taught using Picture and Picture model significantly different than using conventional model. This means that the use of Picture and Picture learning model has a positive effect on the learning result of art class VII SMPN 34 Padang.Keywords: Picture and picture, Motivation, Learning result